2020
DOI: 10.1007/s00217-020-03593-x
|View full text |Cite
|
Sign up to set email alerts
|

Young shoots of red cabbage are a better source of selected nutrients and glucosinolates in comparison to the vegetable at full maturity

Abstract: Cruciferous vegetables are a valuable source of ingredients with health benefits. The most characteristic compounds of cruciferous vegetables with identified anticancer properties are glucosinolates. Young shoots and sprouts of red cabbage are becoming a popular fresh food rich in nutrients and bioactive compounds. The objective of this research was to determine, for the first time in a comprehensive approach, whether young shoots of red headed cabbage are a better source of selected nutrients and glucosinolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 53 publications
6
33
6
2
Order By: Relevance
“…According to Bell and Wagstaff [ 22 ] the white headed cabbage and red headed cabbage are widely consumed and studied crops but has modest total glucosinolates concentrations compared to those of other Brassica crops. In turn, studies by Drozdowska et al [ 23 ] on young 14-day shoots of red headed cabbage demonstrated about four times lower total GLS contents (7.27 µmol/1 g d.m.) than the values obtained in this work.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…According to Bell and Wagstaff [ 22 ] the white headed cabbage and red headed cabbage are widely consumed and studied crops but has modest total glucosinolates concentrations compared to those of other Brassica crops. In turn, studies by Drozdowska et al [ 23 ] on young 14-day shoots of red headed cabbage demonstrated about four times lower total GLS contents (7.27 µmol/1 g d.m.) than the values obtained in this work.…”
Section: Discussionmentioning
confidence: 96%
“…In only one study found on this subject concerning 14-day-old shoots of red cabbage, the main glucosinolates were aliphatic components such as progoitrin, sinigrin, and glucoraphanin which occurred at concentrations above 5.66 µmol/g d.m. (78% of total glucosinolates) [ 23 ]. Seeds have the largest amount of these reserve metabolites, and this is consistent with their roles in plant defense and survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations